Analysis of factors related to the implementation of the surgical safety checklist - Irwadi; Saputra, Andre Utama (International Journal of Health Science and Technology, 2024)
One of the indicators of service quality to patients is patient safety, where hospitals must create a system that reduces and even prevents incidents that threaten patient safety. The operating room is the part of the hospital that most often has problems with patient safety. The 2020 National Committee for Patient Safety (KNKP) report stated that hospital patient safety incidents in West Sumatra Province reached 5%. The purpose of this study is to find out the dominant factor in the implementation of a surgical safety checklist (SSC) in the operating room of Padang Hospital. This study uses a Cross-Sectional quantitative design with a sample of 25 operating room officers. The results showed that there was no relationship between officers' education factors and SSC implementation compliance (p-value = 0.163), there was a relationship between officers' knowledge factors and SSC implementation compliance (p-value = 0.083), there was a relationship between officers' attitude factors and SSC implementation compliance (p-value = 0.002), there was a relationship between officers' working life factors and SSC implementation compliance (p-value = 0.093) and there was a relationship between officers' motivation factors and SSC implementation compliance (p-value = 0.093) value = 0.000). It is hoped that the hospital will always be active in carrying out program strategies to increase officers' compliance with the Surgical Safety Checklist (SSC) by the standards for implementation in the operating room.